Intestinal stem cell response to injury: lessons from Drosophila. - Jiang, H.; Tian, A.; Jiang, J. (Cellular and molecular life sciences. CMLS, 2016)
Many adult tissues and organs are maintained by resident stem cells that are activated in response to injury but the mechanisms that regulate stem cell activity during regeneration are still poorly understood. An emerging system to study such problem is the Drosophila adult midgut. Recent studies have identified both intrinsic factors and extrinsic niche signals that control the proliferation, self-renewal, and lineage differentiation of Drosophila adult intestinal stem cells (ISCs). These findings set up the stage to interrogate how niche signals are regulated and how they are integrated with cell-intrinsic factors to control ISC activity during normal homeostasis and regeneration. Here we review the current understanding of the mechanisms that control ISC self-renewal, proliferation, and lineage differentiation in Drosophila adult midgut with a focus on the niche signaling network that governs ISC activity in response to injury.